Pengaruh Return On Asset, Earning Per Share Dan Net Profit Margin Terhadap Harga Saham - Ali Riza Fahlevi; Teni Eriyanti; Nanda Annisa Putri; Juwita Nur Hassanah; Lidiya Aprilia (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the effect of return on assets, earnings per share, and net profit margin on stock prices. This research uses quantitative methods. The population of this study uses mining sub sector companies listed on the Indonesia Stock Exchange in 2019–2021. The proxy used to measure stock prices is the test of return on assets, earnings per share, and net profit margin on stock prices. The analytical method used in this study uses multiple linear regression analysis using the SPSS version 25 tool. This type of research uses secondary data derived from annual reports of companies listed on the Indonesia Stock Exchange in 2019–2021. The results of the research return on assets (ROA), earning per share (EPS) and net profit margin (NPM) together have a significant positive effect on stock prices.